The Importance of Genetic Testing in the Differential Diagnosis of Atypical TSC2-PKD1 Contiguous Gene Syndrome-Case Series - Petronella Orosz; Zita Kollák; Ákos Pethő; András Fogarasi; György Reusz; Kinga Hadzsiev; Tamás Szabó (MDPI AG, 2023)
Background: In clinical practice, the possible diagnosis of tuberous sclerosis or polycystic kidney disease is primarily based on clinical criteria, which can later be verified by genetic testing. But in the case of TSC2/PKD1 contiguous gene syndrome (TSC2/PKD1-CGS), the renal appearance of the disease is more serious. Therefore, early genetic analysis is recommended. Methods: Herein we present the report of four children with TSC2/PKD1-CGS, one involving the NTHL1 gene. We aim to emphasize the importance of genetic testing in this rare syndrome. Results: During the follow-up of tuberous sclerosis and polycystic kidney disease patients, it is essential to reappraise the diagnosis if the clinical symptoms' appearance or onset time is unusual. Targeted genetic testing is recommended. However, early tumor formation necessitates the extension of genetic analysis. Conclusions: An appropriate evaluation of the phenotype is the cornerstone of diagnosing the rare TSC2/PKD1-CGS with the help of genetic results. In addition, malignant tumors could draw attention to an infrequent large deletion.